The mesoanatomy of the cortex, minimization of free energy, and generative cognition - Wright, James Joseph; Bourke, Paul David (Frontiers in Computational Neuroscience, 2023)
Capacity for generativity and unlimited association is the defining characteristic of sentience, and this capacity somehow arises from neuronal self-organization in the cortex. We have previously argued that, consistent with the free energy principle, cortical development is driven by synaptic and cellular selection maximizing synchronous oscillation, with effects manifest in a wide range of features of mesoscopic cortical anatomy. Here we further argue that in the postnatal stage, as more structured inputs reach the cortex, the same principles of self-organization continue to operate at multitudes of local cortical sites. The unitary ultra-small world structures that emerged antenatally are able to store representations and sequences of spatiotemporal images. Local shifts of presynapses from excitatory to inhibitory cells result in local coupling of spatial eigenmodes and development of Markov blankets, minimizing prediction errors in each unit’s interactions with surrounding neurons. In response to the superposition of inputs exchanged between cortical areas, more complicated, potentially cognitive, structures arise from merging of units with further minimization of free energy, or are competitively eliminated. The trajectory along which free energy is minimized is shaped by interaction with sensorimotor, limbic and brain stem mechanisms, providing a basis for creative and unlimited associative learning